Comparison of Ambulatory Tonometric and Oscillometric Blood Pressure Monitoring in Hypertensive Patients - Hornstrup BG (Integrated Blood Pressure Control, 2020)
Bodil Gade Hornstrup, Jeppe Bakkestrøm Rosenbæk, Jesper Nørgaard Bech University Clinic in Nephrology and Hypertension, Regional Hospital West Jutland and Aarhus University, Holstebro, DenmarkCorrespondence: Bodil Gade HornstrupUniversity Clinic in Nephrology and Hypertension, Regional Hospital West Jutland and Aarhus University, Holstebro, DenmarkEmail bodil.hornstrup@rm.dkAim: Correct measurement of blood pressure (BP) is important for optimal diagnosis and treatment of patients with hypertension. The aim of this study was to compare a wrist-worn device using tonometric measurements of BP to a conventional device using oscillometric measurements of 24 h BP, diagnosing of hypertension, and non-dipping.Methods: One-hundred patients in the Renal Outpatient Clinic had 24 h ambulatory BP monitoring performed with a tonometric device, BPro, and an oscillometric device, A&D, simultaneously.Results: Twenty-four-hour and daytime systolic BP was significantly lower using tonometric monitoring compared to oscillometric (7 and 6 mmHg, respectively, p< 0.001). In the population of patients diagnosed with hypertension, the tonometric device diagnosed 90% of patients with uncontrolled hypertension correctly (positive predictive value), whereas 49% of patients classified as normotensive were uncontrolled hypertensive (negative predictive value). The mean difference between relative nocturnal BP decrease between tonometric and oscillometric was 2± 8% (p< 0.01), and 33% of patients classified as dippers were non-dippers (negative predictive value).Conclusion: Using the BPro device for tonometric monitoring of BP and classification of hypertension and non-dipping in patients diagnosed with hypertension leads to misclassification of patients. Therefore, the BPro device is not suitable for clinical practice in hypertensive patients from a Renal Outpatient Clinic.Keywords: ambulatory blood pressure monitoring, oscillometric, tonometric